Pengaruh Kualitas Pelayanan Terhadap Keputusan Nasabah Dengan Religious Behaviour Sebagai Variabel Moderator (Studi Kasus Pada Produk Tabungan BNI Syariah) - Muniaty Aisyah; Umiyati Umiyati; Riyan Apriansyah (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2017)
The purpose of this study to analyze the effect of the Decision of the Customer Service Quality as Religious Behavior as a moderator variable. The case study on savings products BNI Syariah in Jabodetabek and Banten. The data used in this study are primary data collected from 255 respondents who are customers of BNI Syariah who open a savings account at the office of Greater Jakarta and Banten. The sampling technique used in this study is a convenience sampling method, the data later in the process by using Structural Equation Modeling (SEM) using a 8.80 Lisrel program.The results of this study indicate that the Service Quality directly influence the customer's decision and Religious Behavior moderating influence to the Decision of the Customer Service Quality.